(untitled) (Balthazar, 2025)
This paper, building on Susan Sontag’s seminal works Illness as Metaphor (1978) and AIDS and Its Metaphors (1989), aims to offer a framework for reflecting on the meaning of illness and its metaphorical representations, particularly in the aftermath of the covid-19 pandemic. Sontag’s insights into how illness is often depicted using war metaphors – casting disease as an enemy to be fought – remain highly relevant today. The paper seeks to update these reflections by exploring how the same metaphorical language was employed during the recent pandemic. The objective is to critically examine how the limitations of war-based metaphors fail to capture the full complexity of the phenomena we have experienced. Moreover, it argues for a shift towards a new vocabulary centered on concepts like vulnerability and care, which better express the nuances of collective and individual experiences of illness. This shift in perspective compels us to rethink the metaphors that structure our understanding of illness, advocating for a move away from militaristic language that frames disease in terms of conquest and control, embracing a framework that foregrounds interconnectedness and common vulnerability.